New Ways to Improve Student Material Understanding Using Quizizz During the Covid-19 Pandemic - Wienda Gusta; Elvira Sawitri; Zakirman Zakirman (AL-ISHLAH: Jurnal Pendidikan, 2022)
Covid-19 has had a considerable impact on learning, so to keep improving student learning outcomes, lecturers are required to be more creative in using technology applications such as quizizz. This study aims to see the effectiveness of quizizz in improving student learning outcomes during the implementation of online learning during the Covid-19 pandemic. This type of research is quasi-experimental, involving two sample classes, namely the experimental class and the control class. Sorting the two sample classes using random sampling technique. The data collection instrument used multiple choice tests. The data analysis technique used the t test by first doing the prerequisite tests, namely normality and homogeneity tests. The results of data analysis show that there are significant differences in learning outcomes between students who study using Quizizz and study conventionally. Quizizz has contributed significantly to student learning outcomes, because quizizz is a learning application that is packaged in an attractive manner, has a good graphic design and is automated. Online learning should integrate one of the quizizz applications so that it can motivate students to learn and can directly improve student learning outcomes. The creativity of the teacher in operating the quizizz also influences the course of the learning process.